PENGARUH GEOMETRI PAHAT HSS DAN PARAMETER PERMESINAN TERHADAP KEAUSAN TEPI PAHAT PADA PEMBUBUTAN RATA BAJA KARBON RENDAH (ST 37) DENGAN METODE TAGUCHI - Nur Hayati; Taufiq Hidayat; Gilang Rimba Pamungkas (ELEMEN : JURNAL TEKNIK MESIN, 2022)
The purpose of this study was to determine the effect of tool geometry and determine the optimum parameters for edge wear in the material cutting process (ST 37). The method used is an experimental method by cutting low carbon steel (ST 37) using a High Speed ​​Steel chisel. Variations in tool geometry and machining parameters, namely, spindle rotation: 313 rpm, 457 Rpm, 613 rpm; feeding speed: 0.11 mm/put, 0.22 mm/put, 0.52 mm/put; side cutting edge angle: 12º, 14º, 15º: nose radius: 0.4mm, 0.5mm, 0.8mm. Data analysis using Taguchi and Anova methods. The experimental results show the lowest tool wear is 0.53 mm, and the highest is 1.01 mm. The most influential factors starting from the largest are side cutting edge angle 46.30%, spindle rotation 21.88%, feeding speed 6.79%, and nose radius 1.4%. It was concluded that the most optimum tool wear was 0.53 mm with spindle speed parameters (n): 330 rpm, feed speed (f): 0.52 mm/put, side cutting edge angle (SCEA): 15 , and nose radius 0 ,8º.